Govt spends billions of ringgit to address social problems Adenan - New Sarawak, Tribune (New Sarawak Tribune, 2014)
KUCHING: Social problems such as dumping of babies, smoking, rape, and murder among others being committed by teenagers must be addressed urgently or else it will continue to have negative impact on themselves, the society and the economy, Minister for Special Function Tan Sri Datuk Amar Adenan Satem said yesterday."For example, the problem of drug abuse has caused the government, directly or indirectly RM8.65 billion according to a study conducted by Universiti Utara Malaysia in 2009," he said when speaking at the closing of a three-day state-level 1Malaysia Club Workshop held at Yayasan Sarawak complex near here.